Highly Stable Self-Aligned Ni-InGaAs and Non-Self-Aligned Mo Contact for Monolithic 3-D Integration of InGaAs MOSFETs - Kim, Sanghyeon; Song, Jin Dong; Alam, M. A.; Kim, Hyung-Jun; Kim, Seong Kwang; Shin, Sanghoon; Han, Jae-Hoon; Geum, Dae-Myeong; Shim, Jae-Phil; Lee, Subin; Kim, Hansung; Ju, Gunwu (IEEE journal of the Electron Devices Society, 2019)
Self-heating has emerged as an important performance/reliability challenge for modern MOSFETs. The challenge is further acerbated for III-V transistors, especially when integrated monolithically in a 3-D platform for applications in ultrafast logic, imagers, etc. A key challenge is the difficulty of heat-dissipation through the ultra-thin channels needed to ensure electrostatic integrity of scaled transistors. In this paper, we demonstrate an innovative use of a heat-dissipating shunt of Ni-InGaAs on InGaAs(111) in the S/D extension region, as well as the use of high-conductivity Mo contact to simultaneously improve electrical and thermal stability and heat dissipation in III-V transistors, such that the peak channel temperature is reduced by as much as 25%-30%. Given the exponential temperature sensitivity of transistor reliability, heat shunts will improve transistor lifetime significantly.